Mapping the Tourism Village Potential at Triangle of Diamond Banyuwangi - Ayu Wanda Febrian; Dora Melati Nurita Sandi; Firda Rachma Amalia; Muhamad Ari Perdana (Pencerah, 2023)
Banyuwangi Regency refers to the tourism industry as its leading source of regional income, promoting its tourism destination icon: The Triangle of Diamond. In addition to being an icon, The District Medium-Term Development Plan of Banyuwangi 2016-2021 asserted the Triangle of Diamond as its major project in the Tourism Development Area (TDA). Mount Ijen Crater in Licin District is assigned as TDA I, Plengkung Beach in Tegaldlimo District is designated as TDA II, and Sukamade Beach in Pesanggaran Subdistrict is registered as TDA III. It is expected that tourism is well-developed in rural areas and may increase the prosperity of its people. The analysis of the interactive model of Miles and Huberman (1992), we collected data, gave and recapitulated scores, and determined the final category as a tourist village. The results showed that Kemiren Village in area I, Kalipait Village in area II, and Sumberagung Village in area III are categorized as tourism villages. The three villages have corresponding advantages in cultural aspects, which can then be used to determine a tourism village development strategy. The area I involved the villages of Kemiren, Tamansari, and Kampunganyar. Area II involved Kedungasri, Kalipait, and Purwoagung villages. Area III involved the villages of Sarongan, Sumberagung, and Kedungwungu. Kemiren, Kalipait, and Sumberagung villages have the same advantages in cultural aspects, which can then be used to determine a tourism village development strategy.